Revisiting Lolita: A Postmodern Perspective on Nabokov’s Classic - Liu, Xiaoya (Frontiers in Humanities and Social Sciences, 2024)
This study examines the postmodern features in Vladimir Nabokov’s Lolita, challenging its traditional classification as a modernist novel. The research question explores how Lolita exhibits significant postmodern characteristics, positioning it as a transitional work between modernism and postmodernism. Using a methodology that combines close textual analysis with the application of postmodern literary theory, the study identifies and analyzes two key postmodern aspects of the novel: its representation of postmodern American culture and its questioning of authenticity and reliability. Key findings reveal that Lolita anticipates many postmodern concerns and techniques. The novel’s portrayal of popular culture and the automobile industry embodies postmodern concepts such as consumerism, hyperreality, and the commodification of experience. Nabokov’s depiction of 1950s America presciently captures the emerging postmodern landscape, blurring distinctions between high and low culture and critiquing the media-saturated consumer society. Furthermore, Lolita’s use of an unreliable narrator, its problematization of memory and identity, and its metafictional elements align closely with postmodern literary practices. The novel challenges traditional notions of narrative authority and authenticity, inviting multiple interpretations and resisting closure. The significance of this study lies in its potential to reshape our understanding of both Lolita and the development of postmodern literature. By recognizing the novel’s postmodern elements, we gain a deeper appreciation of its complexity and its influence on subsequent literary developments. This analysis contributes to ongoing debates about the relationship between modernism and postmodernism, suggesting that the boundaries between these movements may be more fluid than previously thought. The study opens new avenues for research in Nabokov studies and postmodern literature, inviting a reconsideration of Lolita’s place in the literary canon and its role in the evolution of 20th-century fiction.